On Hinduism - Doniger, Wendy (Oxford ; New York : Oxford University Press, 2014)
"In this magisterial volume of essays, Wendy Doniger enhances our un derstanding of the ancient and complex religion to which she has devote d herself for half a century. This series of interconnected essays and lectures surveys the most critically important and hotly contested issu es in Hinduism over 3,500 years, from the ancient time of the Vedas to the present day. The essays contemplate the nature of Hinduism; Hindu concepts of divinity; attitudes concerning gender, control, and desire; the question of reality and illusion; and the impermanent and the eter nal in the two great Sanskrit epics, the Ramayana and the Mahabharata. Among the questions Doniger considers are: Are Hindus monotheists or po lytheists? How can atheists be Hindu, and how can unrepentant Hindu sin ners find salvation? Why have Hindus devoted so much attention to the p sychology of addiction? What does the significance of dogs and cows tel l us about Hinduism? How have Hindu concepts of death, rebirth, and kar ma changed over the course of history? How and why does a pluralistic f aith, remarkable for its intellectual tolerance, foster religious intol erance? Doniger concludes with four concise autobiographical essays in which she reflects on her lifetime of scholarship, Hindu criticism of her work, and the influence of Hinduism on her own philosophy of life. On Hinduism is the culmination of over forty years of scholarship from a renowned expert on one of the world's great faiths"--
On being Hindu -- Gods, humans, and anti-gods -- Women and other gen ders -- Kama and other seductions -- Horses and other animals -- Illusi on and reality in the Hindu epics -- On not being Hindu.
Includes bibliographical references (p. 627-648) and index.
Keywords: Hinduism